Introduction: Blockchain for Artistic Research - Łukawski, Adam; Assis, Paulo de (Boca Raton, FL, US CRC Press, Taylor&Francis, 2024)
Book introduction by the editors. This book offers a thorough exploration of the potential of blockchain and AI technologies to transform musical practices. Including contributions from leading researchers in music, arts, and technology, it addresses central notions of agency, authorship, ontology, provenance, and ownership in music.Together, the chapters of this book, often navigating the intersections of post-digital and posthumanist thought, challenge conventional centralized mechanisms of music creation and dissemination, advocating for new forms of musical expression.Stressing the need for the artistic community to engage with blockchain and AI, this volume is essential reading for artists, musicians, researchers, and policymakers curious to know more about the implications of these technologies for the future of music.
FRIS
Editorial review
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music